Predicting Vibrational Spectroscopy for Flexible Molecules and Molecules with Non‐Idle Environments. Issue 4 (16th December 2020) - Kirchner, Barbara; Blasius, Jan; Esser, Lars; Reckien, Werner
Abstract: Flexible molecules and non‐idle environments can present severe problems in the prediction of vibrational spectra. This work focuses on infrared and vibrational circular dichroism for which the latter is extremely sensitive to such complicated situations. Here two possible ways to perform spectroscopy calculations for such situations are investigated. The first approach is based on static quantum chemical calculations employing cluster‐weighting. The second approach is rooted in ab initio molecular dynamics simulations using the time correlations approach. For the present example (( R )‐butan‐2‐ol), excellent spectra from simulations are obtained for gas and bulk, when the former is averaged over trajectories with all possible starting conformers and these are scaled to match the experimental spectrum. The cluster‐weighted approach is inferior to the simulations but still reaches very good results at much less computational cost. A simplified, but computationally less expensive simulation approach is considered by approximating the electric and magnetic moments, which are input quantities in the correlation function, by classical equations and different populations analysis for the required partial charges. The results are inferior to the full simulations but still give satisfying results at the advantage of being much faster to calculate. Abstract : In non‐idle environments problems arise in the determination of vibrational spectra of flexible molecules shown for the example of (R)‐butan‐2‐ol. Ab initio molecular dynamics simulations and cluster‐weighting based on quantum chemical calculations represent two approaches that both achieve excellent results in predicting spectra for such complicated situations compared to their different computational costs.